Thermal characterisation of skin at acupuncture points - Dziuban, Ewa (Видавництво Національного університету “Львівська політехніка”, 2003)
Подано результати досліджень, метою яких є визначення фізичних параметрів в точках акупунктури, як характеризують стан організму людини. У дослідженнях використано температурні та радіаційні метод вимірювань. Представлены результаты исследований, целью которых является определение физических параметров точках акупунктуры, характеризирующих состояние организма человека. В исследованиях использованы температурные и радиационные методы измерений. Recently, the measurement of the signals related to bioelectromagnetic body activity and their interpretation has been of increasing interest. The idea of presented research is to find the possibility of discovering the parameters identifyin the physical properties of the human body at acupuncture points (AP). Thermal characteristics have seemed proper because acupuncture deals with energetic state of organism. For surface body temperature measurement at acupuncture points the non-invasive infra red (IR) radiation method is proposed and its results are presented and discussed.